Injectable Anesthesia for Mice: Combined Effects of Dexmedetomidine, Tiletamine-Zolazepam, and Butorphanol. (22nd January 2017) - Cagle, Laura A.; Franzi, Lisa M.; Epstein, Steven E.; Kass, Philip H.; Last, Jerold A.; Kenyon, Nicholas J.
Abstract : Anesthetic protocols for murine models are varied within the literature and medetomidine has been implicated in the development of urethral plugs in male mice. Our objective was to evaluate the combination of butorphanol, dexmedetomidine, and tiletamine-zolazepam. A secondary objective was to identify which class of agent was associated with urethral obstructions in male mice. BALB/c male (n = 13 ) and female (n = 23 ) mice were assigned to dexmedetomidine and tiletamine-zolazepam with or without butorphanol or to single agent dexmedetomidine or tiletamine-zolazepam. Anesthesia was achieved in 58% (14/24) of mice without butorphanol and in 100% (24/24) of mice with butorphanol. The combination of dexmedetomidine (0.2 mg/kg), tiletamine-zolazepam (40 mg/kg), and butorphanol (3 mg/kg) resulted in an induction and anesthetic duration of 12 and 143 minutes, respectively. Urethral obstructions occurred in 66% (25/38) of trials in male mice that received dexmedetomidine with a mortality rate of 38% (5/13). Tiletamine-zolazepam, when used alone, resulted in a 0% (0/21) incidence of urethral obstructions. Combination use of dexmedetomidine, tiletamine-zolazepam, and butorphanol results in a longer and more reliable duration of anesthesia than the use of dexmedetomidine and tiletamine-zolazepam alone. Dexmedetomidine is not recommended for use in nonterminal procedures in male mice due to the high incidence of urethral obstructions and resultant high mortality rate.